1984
DOI: 10.1515/botm.1984.27.9.437
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in the Levels of Endogenous Cytokinins in Sargassum heterophyllum (Phaeophyceae)

Abstract: A seasonal analysis of cytokinin activity in Sargassum heterophyllum (Turn.) J. Ag. was undertaken. The data thus obtained show that there are pronounced quantitative and qualitative seasonal changes in the cytokinin content of the holdfast, vegetative and reproductive laterals. These changes correspond with the seasonal periodicity of growth, development and reproduction of this alga. Three major peaks of activity were detected: a polar peak, which co-chromatographed with glucosylzeatin, and two non-polar pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
0
15
0
2
Order By: Relevance
“…It may be expected that if plant hormones are important in regulating growth and developmental processes in seaweeds, they will show some seasonal fluctuations in their composition and concentrations. Studies in the 1980s demonstrated there was a seasonal variation in cytokinin-like activity in some brown seaweeds, with an increase in cytokinin-like activity (cytokinin free bases and riboside-like activity) in samples collected during periods of active growth, while there was an increase in cytokinin-O-glucoside-like activity in samples collected during periods of slower growth in Ecklonia maxima (Featonby-Smith & van Staden, 1984), Sargassum heterophyllum (Mooney & van Staden, 1984) and Macrocystis pyrifera (de Nys et al, 1990). Cytokinin-like activity also increased in the vegetative laterals of Sargassum heterophyllum to coincide with gamete release and the onset of regenerative growth, while activity in the reproductive laterals increased to coincide with gamete release and receptacle initiation (Mooney & van Staden, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be expected that if plant hormones are important in regulating growth and developmental processes in seaweeds, they will show some seasonal fluctuations in their composition and concentrations. Studies in the 1980s demonstrated there was a seasonal variation in cytokinin-like activity in some brown seaweeds, with an increase in cytokinin-like activity (cytokinin free bases and riboside-like activity) in samples collected during periods of active growth, while there was an increase in cytokinin-O-glucoside-like activity in samples collected during periods of slower growth in Ecklonia maxima (Featonby-Smith & van Staden, 1984), Sargassum heterophyllum (Mooney & van Staden, 1984) and Macrocystis pyrifera (de Nys et al, 1990). Cytokinin-like activity also increased in the vegetative laterals of Sargassum heterophyllum to coincide with gamete release and the onset of regenerative growth, while activity in the reproductive laterals increased to coincide with gamete release and receptacle initiation (Mooney & van Staden, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the 1980s demonstrated there was a seasonal variation in cytokinin-like activity in some brown seaweeds, with an increase in cytokinin-like activity (cytokinin free bases and riboside-like activity) in samples collected during periods of active growth, while there was an increase in cytokinin-O-glucoside-like activity in samples collected during periods of slower growth in Ecklonia maxima (Featonby-Smith & van Staden, 1984), Sargassum heterophyllum (Mooney & van Staden, 1984) and Macrocystis pyrifera (de Nys et al, 1990). Cytokinin-like activity also increased in the vegetative laterals of Sargassum heterophyllum to coincide with gamete release and the onset of regenerative growth, while activity in the reproductive laterals increased to coincide with gamete release and receptacle initiation (Mooney & van Staden, 1984). The highest cytokinin-activity (free base and riboside-like activity) was detected near the intercalary meristem in the youngest blades of Macrocystis pyrifera, whereas the older portions of the blade had higher levels of cytokinin-O-glucoside-like activity (de Nys et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Its breakdown at the end of August was a natural disintegration presumably related to its annual life form. In its natural bed, it is almost absent from September to November, while during the rest of the year it covers several (Borowczak et al, 1977), Sargassum heterophyllum (Mooney and Van Staden, 1984a) and Ecklonia maxima (FeatonbySmith and Van Staden, 1984). The total species 'final extract' showed enhancement activity in two other assays: germination and growth of bean and lettuce seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…The radish, soybean and lettuce assays contributed a new aspect to the existing cytokinin promoting activities in bananas, potatoes, maize, peppers, tomatoes, pineapples, peaches and oranges (Chapman and Chapman, 1980). Three cytokinin isolation steps were performed in order to compare the activity of the crude extract of Dictyopteris membranacea with previous information (Mooney and Van Staden, 1984a) and to characterize its cytokinin-like activity. The first step (ashing) showed that the aging inhibition is affected by both the ash and organic fractions of the 'final extract'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation